Nanobody-displaying porous silicon nanoparticles for the co-delivery of siRNA and doxorubicin. (2nd November 2020) - Tieu, Terence; Wojnilowicz, Marcin; Huda, Pie; Thurecht, Kristofer J.; Thissen, Helmut; Voelcker, Nicolas H.; Cifuentes-Rius, Anna
Abstract : Targeted delivery of chemotherapeutics to cancer cells has the potential to yield high drug concentrations in cancer cells while minimizing any unwanted side effects. Abstract : Targeted delivery of chemotherapeutics to cancer cells has the potential to yield high drug concentrations in cancer cells while minimizing any unwanted side effects. However, the development of multidrug resistance in cancer cells may impede the accumulation of chemotherapy drugs within these, decreasing its therapeutic efficacy. Downregulation of multidrug resistance-related proteins such as MRP1 with small interfering RNA (siRNA) is a promising approach in the reversal of drug resistance. The co-delivery of doxorubicin (Dox) and siRNA against MRP1 (siMRP1) by using nanoparticles comprised of biocompatible porous silicon (pSi) presents itself as a novel opportunity to utilize the biomaterial's high loading capacity and large accessible surface area. Additionally, to increase the selectivity and retention of the delivery vehicle at the tumor site, nanobodies were incorporated onto the nanoparticle surface via a polyethylene glycol (PEG) linker directed towards either the epidermal growth factor receptor (EGFR) or the prostate specific membrane antigen (PSMA). The nanobody-displaying pSi nanoparticles (pSiNPs) demonstrated effective gene silencing, inhibiting MRP1 expression by 74 ± 6% and 74 ± 4% when incubated with EGFR-pSiNPs and PSMA-pSiNPs, respectively, in prostate cancer cells. The downregulation of MRP1 led to a further increase in cytotoxicity when both siRNA and Dox were delivered in conjunction in both cancer cell monocultures and spheroids when compared to free Dox or Dox and a scrambled sequence of siRNA. Altogether, nanobody-displaying pSiNPs are an effective carrier for the dual delivery of both siRNA and Dox for cancer treatment.